What, if Any, Is the Utility of the Ethics Committees? (BioLaw Journal - Rivista di BioDiritto, 2026)
The question mark of the title accompanies the history of the medico-pharmacological research, and of the related industry, the present protagonist of the scenarios of the activity of the ethics committees, and a most controversial component of the legislations. The administrative-contractual evolution of the ethics committees has marginalized their original profile as bridges between the technical-economic components of the protocols, and the priority the patients’ rights. Most recent scientific literature suggest an increasing perception that substantial changes are needed, and documents an evolution in the direction of providing a positive answer to the question of the title are the exception.
Keywords: ethics committees; medical-pharmacological research; pharmaceutical industry; clinical trial; patient rights; ethical-economic evaluation